STUDI PEMANFAATAN TUMBUHAN SEBAGAI BAHAN OBAT OLEH MASYARAKAT DESA MARIMABATE DI KECAMATAN JAILOLO, HALMAHERA BARAT - Anisatu Z. Wakhidah; Ika Pratiwi; Isma Nur Azzizah (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
An inventory of plants as medicinal material based on local knowledge in east region Indonesia, especially in Halmahera Island, is lacking. This local knowledge, which is inherited orally from elder to their next generation, will be extinct if the information is not documented. Furthermore, plants utilized without conservation effort may cause extinction. According to these reasons, an investigation about local knowledge in plants utilized as medicinal material by Marimabate villagers on Sub district Jailolo, West Halmahera has been conducted in March 2014. The objective of this study is explaining medicinal plants based on local knowledge of Marimabate community and their conservation behaviour. Ethnobotanical data was collected by using semi-structured interview method to shaman and villagers. From the investigation, 21 species of used plant belonged 14 families were recorded. The data showed that leaf was the most often part used among others, they were 16 species. Almost of the using ways of plant was by mixed with warm water then drank to patients. The cureable diasease were 23, such as ‘lidah putih’, ‘bibit-malaria’, menstruation syndrome, and skin burned. The majority medical plants resource was from semi-wild plant (50% species), that showedthe community conservation behavior has been enough applied. Keywords: medical plants, medical material, Marimabate village, West Halmahera